Fabrication of carotenoid enriched Crocus sativus w/o nanoemulsion: Optimization and pharmaceutical characterization - Namrata Aashish Parikh, Komal Patel, Abhay Dharamsi (Journal of Applied Pharmaceutical Science, 2024)
Herbal-based preparations have progressively attracted more interest nowadays due to multiple therapeutic approaches. Major concerns with the use of herbal preparations and their application as functional ingredients are about their stability, solubility, and bioaccessibility. Crocus sativus is one of the crucial nootropic traditional herbs, rich in potential phytochemicals used for the treatment of long-standing disorders. Many studies have suggested that the bioactive present in C. sativus extract may undergo enzymatic degradation in the intestine and hence less bioavailable at the site of action. A novel drug delivery approach to herbal preparation may combat the associated challenge. The present research focuses on the feasibility of developing w/o nanoemulsion incorporating the carotenoid-enriched C. sativus extract by spontaneous emulsification method. Critical process variables were optimized using 32 factorial design with Design of Expert software. The optimized formulation of w/o nanoemulsion comprising 9 mg/ml of C. sativus extracts with 12% internal phase, 21% S-mix, and 67% oil phase produced a globule size of 94.34 nm. The total content present in the nanoemulsion was 83% bioactive determined by the High Performance Liquid Chromatography- Photo Diode Array (HPLC-PDA) method. Further characterization, the Transmission Electron Microscopy (TEM) images showed the overall nanoemulsion system morphology with uniform distribution of globules of the internal phase. The in vitro release of bioactives from developed nanoemulsion showed an initial burst release of 60% at 1 hour following slow drug release. Results demonstrated that w/o nanoemulsion of C. sativus extract overcome the associated challenges and may reserve its space for medicinal application.
Keywords: w/o Nanoemulsion, transmission electron microscopy, bioavailability, pharmaceutical characterization, Crocus sativus extract, HPLC-PDA